Dynamics and Instability of a Vortex Ring Impinging on a Wall (Communications in Computational Physics, 2020)
Dynamics and instability of a vortex ring impinging on a wall were investigatedby means of large eddy simulation for two vortex core thicknesses correspondingto thin and thick vortex rings. Various fundamental mechanisms dictating theflow behaviors, such as evolution of vortical structures, formation of vortices wrappingaround vortex rings, instability and breakdown of vortex rings, and transitionfrom laminar to turbulent state, have been studied systematically. The evolution ofvortical structures is elucidated and the formation of the loop-like and hair-pin vorticeswrapping around the vortex rings (called briefly wrapping vortices) is clarified.Analysis of the enstrophy of wrapping vortices and turbulent kinetic energy (TKE) inflow field indicates that the formation and evolution of wrapping vortices are closelyassociated with the flow transition to turbulent state. It is found that the temporal developmentof wrapping vortices and the growth rate of axial flow generated aroundthe circumference of the core region for the thin ring are faster than those for the thickring. The azimuthal instabilities of primary and secondary vortex rings are analyzedand the development of modal energies is investigated to reveal the flow transitionto turbulent state. The modal energy decay follows a characteristic −5/3 power law,indicating that the vortical flow has become turbulence. Moreover, it is identified thatthe TKE with a major contribution of the azimuthal component is mainly distributedin the core region of vortex rings. The results obtained in this study provide physicalinsight of the mechanisms relevant to the vortical flow evolution from laminar toturbulent state.